Concepções sobre desenvolvimento infantil de enfermeiros que atuam na Estratégia Saúde da Família - Silva, Maria de Fátima de Oliveira Coutinho (2013)
The aim of this research was to analyze the conceptions of child development for nurses working in the Family Health Strategy. This study is anchored in Social-Historical Theory of Vigotski, on the understanding that human development departs from the concept that all human organism is active and establishes successive interactions between the social and the biological basis of human behavior and the approach of the Niche Development of Harkness and Super, which provides insight on the quality of care and possible influences on child development in a given context. We conducted a field study, in the Family Health Units belonging to the Sanitary District III and it was used for data collection a questionnaire that captured the socio-demographic data, and a semi-structured interview, which was analyzed according to Bardin s Thematic Content Analysis. Participants were 38 nurses aged between 41-50 years, 30 were married, with children, and had an average of 20 years graduated. Regarding graduated studies, 35 participants were experts in Public Health and related areas and 32 underwent a Training Development Surveillance. Regarding time of service, 25 had around six years of activity in the Family Health Strategy. Applied and analyzed the interviews emerged a thematic class, ten categories, 27 sub-categories and 1.367 units of analysis. The results showed that the conceptions of nurses on child development are guided by the assumptions of the maturationist theory, transpiring in their speeches the actual theoretical construction of Health Ministry s guidelines for monitoring child development. Apprehends that nurses follow the protocols provided by Health Ministry found in the records or the Child Health Card for the children care and it sustains clearly that among the aspects of development evaluated by nurses predominating maintenance of a natural development conception, based on the existence of an intrinsic force from the child. This study finds these professionals as inconsistent and limited to the ideas of mothers on child development, reports that the process of child development is influenced by the family context, affective and environmental and guides mothers to stimulate child development, according to the contents of the Child Health Card or the age and developmental milestones. The study also reveals that majority of nurses do not realize the systematic care for children up to two years of age, judge their own performance in a fragmented way but realize the need to improve the children care. Apprehends, generally, that there are contradictions in the nurses conceptions, it concludes the need to create spaces for the reflection of these professionals, so that they rethink their conceptions from the context of their work place, and take into account the multiple variables in the understanding of the child, family and development.